2006
DOI: 10.1002/cphc.200600108
|View full text |Cite
|
Sign up to set email alerts
|

Specific Vectorial Immobilization of Oligonucleotide‐Modified Yeast Cytochrome c on Carbon Nanotubes

Abstract: Iso-1-cytochrome c from the yeast Saccharomyces cerevisiae (YCC) contains a surface cysteine residue, Cys102, that is located opposite to the lysine-rich side containing the exposed heme edge, which is the docking site for enzymes. Site-specific vectorial immobilization of YCC via Cys102 on single-walled carbon nanotubes (SWNT) thus provides a selective interface between nanoscopic electronic devices and complex enzymes. We have achieved this by modification of Cys102 with an oligonucleotide (dT(18)). Atomic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…[109] In another study, oligonucleotide-modified yeast cyt c adsorbed strongly to SWNTs, and gave small reversible voltammograms after background subtraction. [130] A number of other heme proteins have been shown to undergo direct electron exchange with carbon MWNT mat electrodes. [37,117,118] However, except in a few special cases (e.g., glucose oxidase), nanotube mat electrodes do not seem to provide significant advantages in reversibility or signal-to-noise ratio compared to the best redox protein films on conventional electrodes.…”
Section: Amperometric and Voltammetric Biosensorsmentioning
confidence: 99%
“…[109] In another study, oligonucleotide-modified yeast cyt c adsorbed strongly to SWNTs, and gave small reversible voltammograms after background subtraction. [130] A number of other heme proteins have been shown to undergo direct electron exchange with carbon MWNT mat electrodes. [37,117,118] However, except in a few special cases (e.g., glucose oxidase), nanotube mat electrodes do not seem to provide significant advantages in reversibility or signal-to-noise ratio compared to the best redox protein films on conventional electrodes.…”
Section: Amperometric and Voltammetric Biosensorsmentioning
confidence: 99%
“…In a subsequent paper, the authors describe the attachment of cytochrome c to single-walled carbon nanotubes in an orientation that will certainly prove appropriate for relaying electrons to redox enzymes. 254 Conductive wiring of an immobilized photosynthetic reaction center 255 or sulfite oxidase 256 to an electrode by horse-heart cytochrome c was also reported. In ref 257, Demaille and co-workers describe a reconstituted photosynthetic electron transfer chain where the proteins were solubilized (rather than adsorbed); they could examine in detail the inter-protein interactions (ferredoxin/PSI and ferredoxin/FNR) and could determine binding and dissociation rates and a shift of the reduction potential of ferredoxin when complexed with FNR.…”
mentioning
confidence: 98%
“…Due to their strong mechanical properties and chemical stability, the carbon nanotubes (CNTs) are seen as very effective support for enzyme immobilization. Enzyme-CNT bionanoconjugates have found applications in biosensors, biofuel cells and biocatalysis [26,27]. It has been demonstrated that the immobilization of enzymes on to the CNT helps in enhancing the overall bioactivity and stability [26,27].…”
Section: Introductionmentioning
confidence: 99%